PROVE: Retrospective, non‐interventional, Phase IV study of perampanel in real‐world clinical care of patients with epilepsy. Issue 2 (20th March 2022) - Wechsler, Robert T.; Wheless, James; Zafar, Muhammad; Huesmann, Graham R.; Lancman, Marcelo; Segal, Eric; Chez, Michael; Aboumatar, Sami; Patten, Anna; Salah, Alejandro; Malhotra, Manoj
Abstract: Objective: To assess retention, dosing, efficacy, and safety of perampanel in a large cohort of patients with epilepsy during routine clinical care. Methods: PROVE was a retrospective, non‐interventional Phase IV study (NCT03208660). Data were obtained retrospectively from the medical records of patients in the United States initiating perampanel after January 1, 2014, according to treating clinicians' recommendation. Retention rate was the primary efficacy endpoint. Secondary efficacy endpoints included median percent changes in seizure frequency per 28 days from baseline, seizure‐freedom rate, and overall investigator impression of seizure effect. Safety endpoints included incidence of treatment‐emergent adverse events (TEAEs). Efficacy and safety were also assessed according to baseline use of enzyme‐inducing antiseizure medications (EIASMs). Results: Overall, 1703 patients were enrolled and included in the Safety Analysis Set (SAS; ≥1 baseline EIASMs, n = 358 [21.0%]; no baseline EIASMs, n = 1345 [79.0%]). Mean (standard deviation [SD]) cumulative duration of exposure to perampanel was 17.4 (15.7) months; mean (SD) daily perampanel dose was 5.6 (2.7) mg. The most frequent perampanel titration intervals were weekly (23.4%) and every 2 weeks (24.7%). Across the SAS, 24‐month retention rate was 48.1% (n = 501/1042). Based on overall investigator impression at the end of treatment, 51.9%, 35.8%, and 12.3% of patients in the SAS experienced improvement, no change, or worsening of seizures, respectively. TEAEs occurred in 704 (41.3%) patients; 79 (4.6%) had serious TEAEs. The most common TEAE was dizziness (7.3%). There was some variation in efficacy according to EIASM use, while retention rates and safety were generally consistent. Significance: In this final analysis of >1700 patients with epilepsy receiving perampanel in routine clinical care, favorable retention and sustained efficacy were demonstrated for ≥12 months.